An Approach to Innovation Potential Evaluation as a Means of Enterprise Management Improving - Iryna Hnatenko (International Journal of Supply and Operations Management, 2020)
Complexity of the enterprise innovative potential as a subject of research and its multifaceted nature cause a large number of approaches to its evaluation. Therefore, an urgent area of research is the development of a comprehensive approach that would promptly and fully diagnose the state of existing innovation potential of the enterprise. This article proposes a methodology for innovation potential evaluation is proposed, based on the resource and productive approaches to its measurement. In accordance with the proposed integrated approach, the following evaluation goals are identified: analysis of the efficiency of using innovative potential and determining the degree of relevance between the existing innovation potential and the selected enterprise development strategy (or new innovation project). As a result of the conducted research, the most informative indicators, characterizing the constituent elements of the innovation potential, have been determined, and on the basis of their use a method of calculating the final indicators of utilization efficiency and relevance of the existing innovation potential of the enterprise has been developed.